(untitled) (Italian Journal of Public Health, 2006)
Background: The Italian healthcare system has two components: public and private healthcare providers. Both deliver services on behalf of and payable by the national health care service. This study explores the relationships between public and private healthcare providers. Methods: The number of hospital admissions and length of stay or number of times the service was accessed stratified by year 2000, 2001, 2002; DRG; type of hospital admission (ordinary or day hospital/surgery); health provider category: public institutions without a specific reference territory, public institutions with a specific reference territory and accredited private institutions and medical or surgery DRGs. A distinction is made between those DRGs defined as belonging to the private sector and those falling within the public sector, assuming there is a majority market portion for services primarily supplied by the private sector. Case-mix index was utelised as the indicator for the complexity of the cases treated and the comparative performance index was used as the indicator for efficiency. Lastly in order to evaluate the services delivered with an inappropriate organizational profile reference is made the rulings defining Essential Level of assistance. Results: The results showed a shift in the reallocation of service volumes for ordinary admissions towards the private sector; the reallocation relates to the volumes but not to the types of cases treated, since the DRG mix remained substantially unchanged over the 3-year period and those DRG that absorb 51% of services were essentially constant. The private sector never achieved a market majority quota but rather controlled market niches with minority quotas. The private institutions treated less complex cases and worked with lower efficiency levels than the public sector. There was also a shift in the distribution of admissions from ordinary admissions to day hospital/day surgery regimes with a growth in the proportion of the latter. Conclusions: The study confirmed the predominance of public healthcare providers in the Italian healthcare system as well as their higher complexity and efficiency levels.